Rapid Skeletal Turnover in a Radiographic Mimic of Osteopetrosis. (December 2014) - Whyte, Michael P; Madson, Katherine L; Mumm, Steven; McAlister, William H; Novack, Deborah V; Blair, Jo C; Helliwell, Timothy R; Stolina, Marina; Abernethy, Laurence J; Shaw, Nicholas J
ABSTRACT Among the high bone mass disorders, the osteopetroses reflect osteoclast failure that prevents skeletal resorption and turnover, leading to reduced bone growth and modeling and characteristic histopathological and radiographic findings. We report an 11‐year‐old boy with a new syndrome that radiographically mimics osteopetrosis (OPT), but features rapid skeletal turnover. He presented at age 21 months with a parasellar, osteoclast‐rich giant cell granuloma. Radiographs showed a dense skull, generalized osteosclerosis and cortical thickening, medullary cavity narrowing, and diminished modeling of tubular bones. His serum alkaline phosphatase was >5000 IU/L (normal <850 IU/L). After partial resection, the granuloma re‐grew but then regressed and stabilized during 3 years of uncomplicated pamidronate treatment. His hyperphosphatasemia transiently diminished, but all bone turnover markers, especially those of apposition, remained elevated. Two years after pamidronate therapy stopped, bone mineral density (BMD) Z‐scores reached +9.1 and +5.8 in the lumbar spine and hip, respectively, and iliac crest histopathology confirmed rapid bone remodeling. Serum multiplex biomarker profiling was striking for low sclerostin. Mutation analysis was negative for activation of lipoprotein receptor‐related protein 4 (LRP4), LRP5, or TGFβ1, and for defective sclerostin (SOST), osteoprotegerin (OPG), RANKL, RANK, SQSTM1, or sFRP1. Microarray showed no notable copy number variation. Studies of his nonconsanguineous parents were unremarkable. The etiology and pathogenesis of this unique syndrome are unknown. © 2014 American Society for Bone and Mineral Research.